2006
DOI: 10.1111/j.1365-2427.2006.01639.x
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of growth rate and body stoichiometry in Daphnia: a role for maintenance processes?

Abstract: 1. The growth rate hypothesis predicts positive relationships among growth rate (l), body RNA (%RNA of dry mass) and body P (%P of dry mass) contents. 2. We tested this within-and across-species by growing five species/clones of Daphnia (Daphnia magna, Daphnia pulex, Daphnia galeata and two isolates of Daphnia pulicaria) with different combinations of food quantity and stoichiometric food quality. 3. Within each species, positive correlations among l, %RNA and %P were seen and across species there was a strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 32 publications
(37 reference statements)
0
34
1
Order By: Relevance
“…1b) as long as S P is within an allowable range (S P,min \ S P \ S P,max ). However, Acharya et al (2004) and Kyle et al (2006) showed that not only the S P but also the growth rate of Daphnia species decreased . c S P plotted against G C according to low, medium, and high food levels.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…1b) as long as S P is within an allowable range (S P,min \ S P \ S P,max ). However, Acharya et al (2004) and Kyle et al (2006) showed that not only the S P but also the growth rate of Daphnia species decreased . c S P plotted against G C according to low, medium, and high food levels.…”
Section: Discussionmentioning
confidence: 92%
“…These values fall within the range of previous studies for Daphnia species (DeMott et al 1998;DeMott et al 2004;Acharya et al 2004;Kyle et al 2006). To convert the body P content into the S P , we assumed that the body C content of Daphnia was 45% of dry mass, because ratio of C to dry mass changes little among Daphnia individuals grown under different food levels (Hessen 1990;Urabe 1988;Acharya et al 2004) except under starved conditions (Hessen 1990).…”
Section: Discussionmentioning
confidence: 95%
“…Also, some Daphnia spp. require relatively higher P and RNA to support maintenance processes than others (Kyle et al, 2006). If D. lumholtzi is one of these species, then it would not be advantageous to bet-hedge in a food-limited condition and maintenance should become a priority over ephippium production.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, herbivore growth responses over a gradient of phosphorous contents in food are expected to show a unimodal response pattern (“stoichiometric knife-edge effect” or “too much of a good thing”) [19]. Levels of P-limitation applied in other studies [18] are typically more severe (C∶P around 1000 for low quality treatments, and around 100 for high quality treatments) and restrict growth responses to the range where obvious P-limitation occurs. In contrast, C∶P ratios in our study ranged from moderate limitation (400) to sufficient (200) or perhaps even surplus (50), where growth may no longer be limited by phosphorus.…”
Section: Discussionmentioning
confidence: 99%
“…Maintenance is expected to largely depend on carbon, but it may also require nutrients such as phosphorus [18], [25]. One way to examine the possible role of carbon and phosphorus in maintenance is to compare the effects of different phosphorus levels of food (C∶P ratios) on the minimal residual food concentrations.…”
Section: Introductionmentioning
confidence: 99%